Implementation of Complete Qur'an Reading Movement (GETBA) in Senior High Schools in Simpang Kiri District - Azizah Hanum OK; Yusnaili Budianti; Mustafa (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to analyze: 1) the GETBA program in high schools in Simpang Kiri District, 2) the implementation of GETBA in high schools in Simpang Kiri District, 3) the evaluation system for GETBA in high schools in Simpang Kiri District,4) supporting and inhibiting factors in implementation of GETBA) in high schools throughout Simpang Kiri District. The type of research used is qualitative research. This research was located at 2 (two) high schools in Simpang Kiri District, Subulussalam City, Aceh Province, namely SMAN 1 Simpang Kiri and SMAN 1 Subulussalam. The results of the research show that: The GETBA program or Movement to Completely Read the Al-Qur'an is a program in the PAI field of the Regional Office of the Ministry of Religion of Aceh Province, including Simpang Kiri sub-district, Subulussalam City. This program will be launched at the end of 2022. The supporting factors are that students are easy to direct, parents of students provide financial support, enthusiastic teachers, and the presence of students' strong will/intention in reading the Koran. Meanwhile, the inhibiting factors are the existence of students who have just started reading the Koran, the feeling of shame and laziness among students and the existence of students who do not yet know Arabic or Hijaiyah.